THE FACTORS THAT INFLUENCE THE DIVIDEND POLICY AND ITS IMPACT ON FUTURE EARNINGS GROWTH OF COMPANY IN CONSUMER GOODS INDUSTRY SECTOR LISTED IN BEI DURING 2010-2014 PERIOD - Ricky Setiawan; Werner R. Murhadi; Bertha Silvia S. (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
This study aimed to analyze the factors that influence the dividend policy and its impact on future earnings growth. Variable used include size, leverage¸ lagged dividend policy, growth, and profitability. This study uses a quantitative approach to the analyze and use two stages least square as a model. This study used a sample of firm in the sector of consumer goods industry that distribute the minimum dividend 2 times on 2010-2014. The results showed that variable size, dividend payment of the previous period, and profitability has a positive and significant impact on dividend policy. While variable growth leverage and significant negative effect on dividend policy. For the second model variables profitability have a significant negative effect on the future earnings growth. While the variable leverage has significant negative effect on the future earnings growth. Other variables such as dividend policy, size, and growth have no significant effect on future earnings growth.